Overstating the lack of evidence on suicide risk assessment - Wolf, A; Fazel, S (Royal College of Psychiatrists, 2017)
Chan and colleagues provide an overview of risk factors and risk scales for suicide following self-harm (1). However, their conclusions go beyond their review findings and we think discounting the potential value of such tools on the basis of imperfect tools designed for other purposes is premature.